Consultation workshop report on nutrition-sensitive agri-food systems interventions priorities in the Mekong Delta - Duong, Thanh; Huynh, Tuyen; Nabuuma, Deborah; Hoang, Ky; Truong, Mai; Tuan, Phuong; Dinh, Phuong (2023)
On December 8, 2023, the National Institute of Nutrition (NIN) and the Alliance of Bioversity International and International Center for Tropical Agriculture (The Alliance of Bioversity International and CIAT) co-organized the consultation workshop in Can Tho, Vietnam, to share the preliminary results regarding data on food consumption and diets, literature, and policy reviews related to nutrition-sensitive agri-food systems in the Mekong Delta and to gather feedback and input from stakeholders representing various universities, organizations, and government agencies to further validate these results. More than 30 workshop participants (more than 80% are women) who are professionally and actively involved in agriculture, health, and economic sectors attended. The workshop served as a platform for food system actors to share information on current initiatives and networks linked to nutrition-sensitive agri-food systems in the Mekong Delta of Vietnam. It also allowed NIN, the Alliance of Bioversity International and CIAT, and their partners to present and discuss the initial outcomes on data, literature, and policies that promote nutrition-sensitive agri-food systems in the Mekong Delta region of Vietnam. The objectives of the workshop are to: 1. Share some preliminary results on food consumption, nutrition status and the trends in diets of people in the Mekong Delta, Vietnam that extracted from the General Nutrition Surveys in Vietnam in 2010 and 2020. 2. Present and validate the results of the literature and policy review of the nutrition-sensitive agri-food systems in Vietnam. 3. Gather feedback from the stakeholders on intervention priorities of nutrition-sensitive food systems in the Mekong Delta of Vietnam The consultation workshop was a successful and productive event that contributed to the process of finalizing the policies and literature review on nutrition-sensitive agri-food systems in the Mekong Delta Region of Vietnam. The workshop also fostered a participatory and collaborative approach among the researchers, government officials, and local stakeholders, who shared their experiences, feedback, and input on the content and implementation of relevant interventions on nutrition-sensitive agri-food systems. The workshop emphasized the need to integrate nutrition-sensitive agri-food systems approaches into policy and practice and to involve multisector actors in agri-food system transformation to address related challenges in the region. The workshop is an important activity in the AMD Initiative, which aims to support the food and nutrition security and resilience of the Asian mega-deltas.